Analisis Perilaku Ekonomi Rumah Tangga Pengrajin Gula Aren Di Kabupaten Lebak, Banten - Andjar Astuti; Ratna Mega Sari; Asih Mulyaningsih (Jurusan Agribisnis Fakultas Pertanian Universitas Sultan Ageng Tirtayasa, 2019)
The growth of palm sugar production in Lebak Regency as a center of palm sugar in Banten Province continues to show a positive trend so that it is an important source of income for many households in Lebak Regency. The purpose of this study was to analyze the household economic behavior of palm sugar farmers which included the outlay of working time of farmer household members, production and income and household consumption expenditure of palm sugar craftsmen in Lebak Regency. The research data used are primary and secondary data which are processed descriptively and quantitatively. Quantitative data is processed using a simultaneous equation model with the least squares method (2SLS). The outpouring of work on aren business is significantly affected by the number of sugar palm trees owned and the outpouring of work time on non-aren businesses. Job outpouring on non-aren business is significantly affected by income from non-aren business while other variables do not significantly influence. Variables that significantly influence palm sugar production are production costs and the number of sugar palm trees owned. While the outpouring of aren business work time has no significant effect on production.